The Relationship between Spiritual Intelligence, Emotional Intelligence and Intellectual Intelligence with Communication Ethics of Students at IAIN Bone - Kasmah Kasmah; A Nur Aisyah Rusnali (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2020)
This article aims to analyze the spiritual intelligence on the students’ Communication Ethics, emotional intelligence on the students’ communication ethics, spiritual, emotional, and intellectual intelligence on students’ communication ethics at IAIN Bone. This article used comparative study in using Pearson's correlation technique product moment .The results showed the results of testing with a regression model showed that spiritual, emotional and intellectual intelligence together were significant to the ethics of communication at a real level of five percent. It can be seen from the probability value below alpha five (5) percent, which is equal to 0,000. This means that the proposed alternative hypothesis (H4) is accepted and reject H0. Thus, a joint change of the three types of intelligence will be followed by an increase in communication ethics for IAIN Bone students. Keywords: Spiritual Intelligence, Emotional Intelligence, Intellectual Intelligence, Communication Ethics